2015
DOI: 10.1097/prs.0000000000001267
|View full text |Cite
|
Sign up to set email alerts
|

A Cost-Utility Analysis Comparing the Sartorius versus the Rectus Femoris Flap in the Treatment of the Infected Vascular Groin Graft Wound

Abstract: The rectus femoris flap in the treatment of the infected vascular groin graft is a cost-effective option compared with the sartorius flap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…21,[24][25][26][27][28] The end states of sartorius flap reconstruction, excision of graft and axillaryfemoral bypass, amputation, and death were obtained from our groups' previously published work. 29…”
Section: Decision Model and Probabilitiesmentioning
confidence: 99%
“…21,[24][25][26][27][28] The end states of sartorius flap reconstruction, excision of graft and axillaryfemoral bypass, amputation, and death were obtained from our groups' previously published work. 29…”
Section: Decision Model and Probabilitiesmentioning
confidence: 99%
“…1,12,17,28 Chatterjee A et al reported that the rectus femoris muscle flap is more cost effective when used to treat the infected vascular groin graft wound. 29 Ryu DY et al mentioned that Sartorius muscle flap lacks bulk and has a limited arc rotation, making it suboptimal for large wounds, in comparison to rectus femoris muscle flap, but the rectus femoris muscle flap needs a longer separate incision in the thigh. 16 They stated also that due to the segmental blood supply arising from superficial femoral artery, some vascular surgeons might hesitate to use the Sartorius muscle flap in patients with an occluded superficial femoral artery.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in comparing costs, the RFF appears to be a cost-effective choice for coverage of complex groin wounds. In a series of 296 patients undergoing 62 RFFs and 234 sartorius flaps, Chatterjee et al 20 reported a 14% major complication rate (defined as graft excision, amputation, or death) with sartorius flaps and only a 9% major complication rate for RFFs. Based on a oneway sensitivity analysis, these investigators determined that sartorius flaps would become cost-effective only if their major complication rate fell below 9%.…”
Section: Journal Of Vascular Surgerymentioning
confidence: 99%